Airway management in patients with maxillofacial trauma – A retrospective study of 177 cases - Raval, Chetan B. (Medknow Publications, 2011)
BACKGROUND: Airway management in maxillofacial injuries presents with a unique set of problems. Compromised airway is still a challenge to the anesthesiologist in spite of all modalities available. Maxillofacial injuries are the result of high-velocity trauma arising from road traffic accidents, sport injuries, falls and gunshot wounds. Any flaw in airway management may lead to grave morbidity and mortality in prehospital or hospital settings and as well as for reconstruction of fractures subsequently. METHODS: One hundred and seventy-seven patients of maxillofacial injuries, operated over a period of one and half years during July 2008 to December 2009 in Al-Nahdha hospital were reviewed. All patients were reviewed in depth with age related type of injury, etiology and techniques of difficult airway management. RESULTS: The major etiology of injuries were road traffic accidents (67%) followed by sport (15%) and fall (15%). Majority of patients were young in the age group of 11-30 years (71 %). Fracture mandible (53%) was the most common injury, followed by fracture maxilla (21%), fracture zygoma (19%) and pan-facial fractures (6%). Maxillofacial injuries compromise mask ventilation and difficult airway due to facial fractures, tissue edema and deranged anatomy. Shared airway with the surgeon needs special attention due to restrictions imposed during surgery. Several methods available for securing the airway, both decision-making and performance, are important in such circumstances. Airway secured by nasal intubation with direct visualization of vocal cords was the most common (57%), followed by oral intubation (17%). Other methods like tracheostomy and blind nasal intubation was avoided by fiberoptic bronchoscopic nasal intubation in 26% of patients. CONCLUSION: The results of this study indicated that surgically securing the airway by tracheostomy should be revised compared to other available methods. In the era of rigid fixation of fractures and the possibility of leaving the patient without wiring an open mouth and alternative techniques like fiberoptic bronchoscopic intubation, it is unnecessary to carry out tracheostomy for securing the airway as frequently as in the past.